2012
DOI: 10.1038/srep00664
|View full text |Cite
|
Sign up to set email alerts
|

Nettle as a distinct Bronze Age textile plant

Abstract: It is generally assumed that the production of plant fibre textiles in ancient Europe, especially woven textiles for clothing, was closely linked to the development of agriculture through the use of cultivated textile plants (flax, hemp). Here we present a new investigation of the 2800 year old Lusehøj Bronze Age Textile from Voldtofte, Denmark, which challenges this assumption. We show that the textile is made of imported nettle, most probably from the Kärnten-Steiermark region, an area which at the time had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Fibrillar orientation is a characteristic feature for a species and serves as an aid for identification (Herzog, 1955). For example, knowledge about the fibrillar orientation of a fibre and the presence of calcium oxalate crystals in the associated tissue makes it possible to conclusively distinguish nettle/ramie fibres from hemp, flax and jute Bergfjord et al, 2012). The composition of fibre cells in most common bast textile plants are in fact very similar.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrillar orientation is a characteristic feature for a species and serves as an aid for identification (Herzog, 1955). For example, knowledge about the fibrillar orientation of a fibre and the presence of calcium oxalate crystals in the associated tissue makes it possible to conclusively distinguish nettle/ramie fibres from hemp, flax and jute Bergfjord et al, 2012). The composition of fibre cells in most common bast textile plants are in fact very similar.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recovery of flax seeds from other Bronze Age sites would suggest that flax was employed for weaving along with wool (Cardarelli et al 2009), rather than hemp (attested by the Montale pollen record - Mercuri et al 2006a) that was more suitable for rope production. Although, it cannot be excluded the use of wild plants for yarn, such as nettle, now recognised as an important textile plant in Europe during the Bronze Age (Bergfjord et al 2012), and documented at Montale within the anthropogenic pollen indicators (Mercuri et al 2012).…”
Section: Iansa 2017 • Viii/2 • 175-186mentioning
confidence: 99%
“…Similarly, we could assume a high presence of Urtica dioica seeds, which, on the one hand, is a typical representative of alder carr species. On the other hand, a recent study from Denmark has suggested nettles as an important Bronze Age plant exploited for textile production in their natural habitat (Bergfjord et al 2012). Chenopodium album agg.…”
Section: Plant Macrofossils Recordsmentioning
confidence: 99%